Progay/antigay : the rhetorical war over sexuality - Smith, Ralph R. (Rhetoric & society (Thousand Oaks, CA) ;, 2000)
"Combining humanistic rhetorical criticism with social scientific concepts, Ralph R. Smith and Russel R. Windes examine how the discourse of the progay/antigay debate shapes the self-understanding and strategies of the two opposing sides. The struggle over issues such as lesbians and gay men serving openly in the military, same sex marriage, and inclusion of "sexual orientation" in anti-discrimination and hate crime laws has evolved along with the development of rival progay and traditionalist antigay communities. In the process of presenting their arguments to the wider society, the two sides exercise extraordinary influence on each other. As a result of public policy debates, the progay movement has moved toward an essentialist, non-sexual identity, while the traditionalists have shifted toward a secular public self-representation. Progay/Antigay also analyzes the internal disagreements within the two movements." --Book Jacket.